Faculty roles and changing expectations in the new age - Inoue, Yukiko 1953- (IGI Global, 2019)
"This book provides theoretical understanding of the essential link between ongoing changes in institutions and changes in faculty roles, a link that is important for understanding teaching and learning in general, and for understanding learner-centered pedagogical approaches. It also provides course designs and pedagogical approaches that place faculty in the role of leaders and coaches for learning"...Provided by publisher